Determining the Leadership Order of the Clinically Responsible Nurse Working in a University Hospital - Yücel, Ilknur; Cihangiroğlu, Nuray (KHD-Production, 2024)
This study aims to determine the leadership orientations of clinical chief nurses. In the descriptive study, the G-Power 3.1.9.4 program was used to calculate the sample size and the number of people planned to be included in the study was calculated as 50 with 5% error and 95% power. In this direction, all (50) clinical nurses working in a university hospital between 10.05.2023 and 30.05.2023 will form the study sample group. The data of the study will be collected from individuals with a socio-demographic